Analisis Dampak Pelanggaran Lalu Lintas terhadap Keselamatan Masyarakat dan Upaya Mempromosikan Nilai-Nilai Kemanusiaan dan kesadaran berkendara (International Forum of Researchers and Lecturers, 2024)
Traffic violations are an integral part of modern life. Traffic is needed along with the development of transportation, human mobility, and road use. This development has raised attention to aspects of traffic safety so that traffic rules have been issued to maintain security, order and smooth traffic. The lack of awareness among the public regarding traffic laws can be seen in behavior such as the increasing number of traffic violations by motorbike and car drivers. The aim of this research is to determine the impact of traffic violations and applicable penalties as well as efforts to promote human values. The method used in this research is a descriptive qualitative method, where the research will contain data excerpts regarding traffic violations related to human values. The research results obtained were based on direct observation, there were several cases including disobeying traffic signs, not wearing a helmet, not wearing vehicle plates and going against the direction.